Consumer behavior and its process in making their buying decisions. The new consumer´s path - Gonzales Sulla, Alicia Elizabeth (2021)
We are facing a very dynamic market, to which is added the digital transformation and the effect of the COVID-19 pandemic, our consumer is much more informed and demanding, whose buying decision will depend not only on him but on their interactions with other consumers and the different ways of interacting using digital media. Therefore, the main objective of the article is to review the change that consumer behavior and its buying decision process have been having and how companies must take into account the new path of the consumer and thus develop their marketing strategies that stimulate the buying decision by achieving an experience with the consumer capable of creating deep emotional bonds and that concludes with the choice and loyalty of the brand; for this reason a matrix table has been prepared that reflects the evolution of this consumer, so the probability of doing a buying it again will reassure the permanence of the company in the market.